2021
DOI: 10.1093/ajcn/nqab259
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized trial of a novel lifestyle intervention compared with the Diabetes Prevention Program for weight loss in adult dependents of military service members

Abstract: Background Lifestyle interventions are the first-line treatment for obesity, but participant weight loss is typically low. Objectives We evaluated the efficacy of an alternative lifestyle intervention [Healthy Weight for Living (HWL)] compared with a modified Diabetes Prevention Program (m-DPP). HWL was based on a revised health behavior change model emphasizing hunger management and the development of healthy food preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…These results are consistent with the limited existing evidence supporting the beneficial effects of behavioral weight loss interventions promoting nutritional education and behavior change on dietary behavior, diet quality, and/or adherence to the Mediterranean diet [29][30][31][32][33]. Patnode et al [29], in a systematic review for the U.S. Preventive Services Task Force, found that healthful diet interventions in adults without known cardiovascular disease risk factors were related to reduced total energy and saturated fat intake and increased fiber and fruits and vegetables consumption.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are consistent with the limited existing evidence supporting the beneficial effects of behavioral weight loss interventions promoting nutritional education and behavior change on dietary behavior, diet quality, and/or adherence to the Mediterranean diet [29][30][31][32][33]. Patnode et al [29], in a systematic review for the U.S. Preventive Services Task Force, found that healthful diet interventions in adults without known cardiovascular disease risk factors were related to reduced total energy and saturated fat intake and increased fiber and fruits and vegetables consumption.…”
Section: Discussionsupporting
confidence: 90%
“…Instead, alternative approaches, such as Mediterranean diets and other dietary strategies focusing on nutritional education and behavior change, have been proposed as potential strategies of choice for OSA management [26][27][28]. Still, although effective at improving dietary behaviors in persons with and without cardiovascular risk factors and other conditions [29][30][31][32][33], there is no evidence to date on the effects of this approach on the unhealthy dietary behaviors and poor quality of the diet commonly found in patients with OSA [34][35][36]. Similarly, and consecutively, there is no study investigating the association of changes in dietary behaviors and changes in OSA severity and related outcomes, such as body weight and composition in adults with OSA and who are overweight/have obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Das et al conducted a 12-month parallel randomized controlled trial in free-living adults comparing two weight-loss interventions with the common goal of reducing calories (500–1000 kcal/day) and achieving physical activity goals (150 min/week), but one emphasized weight loss through tracking food and physical activity (modified Diabetes Prevention Program [m-DPP]) and the other emphasized behavior change (stress management, mindful eating, etc.) (Healthy Weight for Living [HWL]) [ 50 ]. Both interventions (m-DPP and HWL) significantly improved weight (− 7.32 and 7.46 kg) and cardiometabolic risk factors (LDL-C [− 10 and − 15 mg/dL], triglycerides [18 and − 21 mg/dL], and glucose [− 3 and − 6 mg/dL]) from baseline with similar non-significant improvements in sleep, emotional, and general health.…”
Section: Healthy Weightmentioning
confidence: 99%
“…In the two randomized trials evaluating its weight loss effectiveness, HWL resulted in weight loss of 8.0 kg 9 and 8.5%. 8 However, neither of these trials was designed to provide a rigorous evaluation of HWL against a traditional program.…”
Section: Introductionmentioning
confidence: 99%
“…Members of our team developed the Healthy Weight for Living (HWL) program, 7,8 which is based on a revised health behaviour change model with emphasis on biological factors that influence energy regulation (i.e., reducing hunger and food craving) and reducing participant burden (i.e., minimal emphasis on logging activities), as well as the psychological, environmental, and practical factors that are recognized in traditional models. In the two randomized trials evaluating its weight loss effectiveness, HWL resulted in weight loss of 8.0 kg 9 and 8.5% 8 . However, neither of these trials was designed to provide a rigorous evaluation of HWL against a traditional program.…”
Section: Introductionmentioning
confidence: 99%